FMBEM analysis of sound scattering from a damping plate in the near field of a hydrophone. - Wilkes, Daniel; Alexander, P.; Duncan, Alexander (Acoustical Society of Australia, 2012)
As part of research into the effect of underwater noise on the communication between an under-ice Autonomous Underwater Vehicle (AUV) and it’s stationary launch vessel (the Aurora Australis), fast multipole boundary element method (FMBEM) acoustic modeling was conducted. In particular, a steel damping plate with a complex 3-dimensional structure was modeled (using up to 1.6 x 10 5 boundary elements) and the effect of sound scattering from a pinger near the ship was determined at the receiver hydrophone, which was in close proximity to the damping plate. The direct incident field from the pinger was modeled as a plane wave at a number of incidence angles (to account for the depths to which the hydrophone was lowered) and over a range of frequencies up to the pinger frequency of 10kHz. This paper presents these results and discusses some of the interesting effects observed at the ‘non-unique’ frequencies when using the different methods available to provide stability to the numerical solution. Thus far, the modeling conducted for the damping plate has treated the object as rigid. The FMBEM code being developed at CMST now has the capability to model fully coupled fluid-structure interactions and some initial results from treating the damping plate as elastic are also presented.